Comparison studies on the anticorrosion and overall performance of solvent/water based poxy-copper reinforced composite coatings - Ammar, S.; Ramesh, K.; Azman, N.A.N.; Vengadaesvaran, B.; Ramesh, S.; Arof, Abdul Kariem (American Scientific Publishers, 2016)
The influence of using two types of carrier agent namely, water and solvent, on the overall performance of epoxy resin has been investigated. Furthermore, four different loading rates of copper pigments (Cu) have been successfully embedded into two developed polymeric matrices and the changes occurred in the structure, thermal, fouling ability, morphology, and the anticorrosion performance have been studied. Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), field immersion test, scanning electron microscope (SEM), and electrochemical impedance spectroscopy (EIS) were used to evaluate the formulated coating systems. The results revealed that, the incorporation of Cu pigments did not significantly affect the efficiency of the room temperature curing process and further led to enhancement on the thermal stability of both developed epoxy resins. However, utilizing Cu pigments with solvent based epoxy (SB) showed better antifouling and anticorrosion properties compered to Cu composites prepared with water based epoxy resin (WB). The electrochemical behavior up to 30 days of immersion in 3.5% NaCl solution confirmed that the SB resin loaded with Cu pigments at 10% PVC, SB 10, demonstrated excellent barrier and anticorrosion properties. Neat WB coating (WB 0) was found to have the best performance among all WB coating systems.